Using Phenomenological Methodology with Thematic Analysis to Examine and Reflect on Commonalities of Instructors’ Experiences in MOOCs - Chi-Cheng Chang; Yao-Hua Wang (Education Sciences, 2021)
Instructors’ experiences in MOOCs assist their curriculum development and teaching skills as well as professional growth, which is seldom explored. The study examined and reflected on the commonalities of instructors’ experiences in Massive Open Online Courses (MOOC) based on phenomenological methodology with thematic analysis. By summarizing the commonalities in phenomenology from the implicit experiences of the instructors who were interviewed, commonalities of MOOC instructors’ experiences were found to be the following: (1) affinity—knowing how to provide MOOC material that is approachable; (2) ability to tell a story—knowing how to write and direct a video that contains a story or scenarios for classes as innovative teaching; (3) macro attitude—broadening a learner’s horizon is more important than lecturing on knowledge; (4) altruism—concerning the welfare of students rather than personal fame and fortune; and (5) learning by doing—having a passion for innovative teaching and bravely implementing it. Finally, several suggestions and inspirations were given based upon the reflections on the commonalities of MOOC instructors’ experiences.